Peculiarities of Tourist Terminology: on the Material of Formal and Structural Analysis - Safarova Nigina Mamurjonovna (Universitas Muhammadiyah Sidoarjo, 2020)
This article deals with the peculiarities of English tourism terminology in terms of formal and structural analysis of a sample of English tourism terms with a total of 20 terminological units. According to the author of the article, knowledge of English terminology in its field of activity is necessary for every specialist who seeks to develop and reach new levels of international understanding and cooperation. At the same time, the knowledge of English terminology in the sphere of tourism is intended to become the basis for this growth, as it promotes professional communication at a worthy specialist level in any country and allows being a self-sufficient member of modern society while travelling abroad for business or personal purposes. Tourism is a global infrastructure, and the terminology that serves it is also international. Thus, when studying English terminology of the tourism industry, any specialist in this sphere of activity has additional opportunities for professional growth: business trips within the framework of congress tourism; expansion of general outlook and erudition within the framework of excursion tourism; walking expeditionary tours as a corporate rest with the aim of uniting a team of employees through sports activities within the framework of sports tourism. Tourism opportunities are diverse both for specialists and for any person who seeks to improve and develop himself. To take full advantage of these opportunities, knowledge of English tourism terminology allows.